Atlantic salmon type I interferons - induction and antiviral activity - Svingerud, Tina (2013)
The papers of this thesis are not available in Munin: I. : Kristel Berg, Tina Svingerud, Baojian Sun, Børre Robertsen. An antiserum against Atlantic salmon IFNa1 detects IFN and neutralizes antiviral activity produced by poly I: C stimulated cells. Developmental & Comparative Immunology. Volume 33, Issue 4, April 2009, Pages 638-645. Available in Developmental & Comparative Immunology. Volume 33, Issue 4, 2009, Pages 638-645 II.Silje Lauksund, Tina Svingerud, Veronica Bergan, Børre Robertsen. Atlantic salmon IPS-1 mediates induction of IFNa1 and activation of NF-κB and localizes to mitochondria. Developmental & Comparative Immunology. Volume 33, Issue 11, November 2009, Pages 1196-1204. Available in Developmental & Comparative Immunology. Volume 33, Issue 11, 2009, Pages 1196-1204 III. Tina Svingerud*, Terese Solstad*, Baojian Sun, May Liss J. Nyrud, Øyvind Kileng, Linn Greiner-Tollersrud, Børre Robertsen. Atlantic Salmon Type I IFN Subtypes Show Differences in Antiviral Activity and Cell-Dependent Expression: Evidence for High IFNb/IFNc–Producing Cells in Fish. The Journal of Immunology. Volume 189, Issue 12,December 2012, Pages 5912-5923. Available in The Journal of Immunology. Volume 189, Issue 12, 2012, Pages 5912-5923 IV. Tina Svingerud, Jenni Kristin Holand, Børre Robertsen. Infectious salmon anemia virus (ISAV) is transiently inhibited by Atlantic salmon type I interferon. (Manuscript). Published version available in Virus Research Volume 177, Issue 2, 2013, Pages 163–170